Mo3P/Mo heterojunction for efficient conversion of lithium polysulfides in high-performance lithium-sulfur batteries - Sun, Zhongpeng; Wang, Yuanhao; Xu, Jie; Wang, Xia (Frontiers in Chemistry, 2024)
Realizing efficient immobilization of lithium polysulfides (LiPSs) as well as reversible catalytic conversion between LiPSs and the insoluble Li2S is vital to restrain the shuttle effect, which requires highly reactive catalysts for high-performance Li-S batteries. Here, three-dimensional ordered porous Mo-based metal phosphides (3DOP Mo3P/Mo) with heterogeneous structures were fabricated and utilized as separator-modified coatings for Li-S batteries to catalyze the conversion of LiPSs. The adsorption, catalytic and electrochemical performance of the corresponding cells were compared among 3DOP Mo3P/Mo and 3DOP Mo, by kinetic and electrochemical performance measurements. It was found that the cell with 3DOP Mo3P/Mo modified separator deliver better electrochemical performance, with a high specific capacity of 469.66 mAh g−1 after 500 cycles at a high current density of 1°C. This work provides an idea and a guideline for the design of the separator modification for high-performance Li-S batteries.